Prácticas de enseñanza de iniciación a la lectoescritura en el nivel inicial II en el Centro de Desarrollo Infantil Mis Primeras Huellas - Nieto Larrea, Karen Alejandra (2016)
This work titration was performed with the purpose of analyzing teaching practices in the introduction to literacy in Early Childhood Education II at the Child Development Center My First Footprints. The area Language is very important as it is accessed in school curricula, is present throughout all the years of compulsory schooling .As a result of research nonexistent investigations it was found in our country about teaching practices, not there is no paper studies on which educators can support us in said subject. For this reason, one of the objectives is to create this aid instrument and experiences to the classroom. The way it was done was from the qualitative approach through field diary and observation sheets. The analytical emphasis of this study allowed characterizing the practice of teaching faculty in the planning, methodological structure, work organization, teacher-student interaction in the activities, assessment strategies and type of academic tasks. The results of the investigation established that the practices of teaching literacy are routed from the very formation of the teaching to the specialties of the Child Development Center where he works.